Assessment of the thermodynamic probability of naphthenes formation by hydrogen transfer reactions from cycloolefins, during their processing on zeolite; Химия и химическая технология в XXI веке; Т. 2 - Bagdasaryan N. S. (Химия и химическая технология на иностранном языке (английский), 2021)
Заглавие с титульного экрана